2021
DOI: 10.1021/acs.inorgchem.1c01827
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks Featuring 18-Connected Nonanuclear Rare-Earth Oxygen Clusters and Cavities for Efficient C2H2/CO2 Separation

Abstract: Two rare-earth (RE) metal–organic frameworks (MOFs) formulated as {(Me2NH2)2[RE9(μ3-OH)8(μ2-OH)3(DCPB)6(H2O)3]} n (RE = Y3+ and Tb3+; termed JXNU-10) built from a triangular 3,5-di­(4′-carboxylphenyl)­benzoic acid (DCPB3–) ligand are presented. JXNU-10 features the rarely observed 18-connected nonanuclear [RE9(μ3-OH)8(μ2-OH)3] clusters, one-dimensional-nanosized tubular channels, and trigonal-bipyramidal cavities. The presence of the high-nuclear RE-oxo clusters and the robust coordination bonds between the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…To widen their application scope, it is highly desirable to fabricate robust LOFs with permanent porosity after excluding the guest molecules. To this end, effective methods have been developed, including utilization of discrete highly connected multinuclear clusters and infinite rod-shaped chains as inorganic SBUs. For example, by employing 2-fluorobenzoic acid as a fluorinated modulator, the Eddaoudi group fabricated a series of LOFs on the basis of a 12-connected [Ln 6 (μ 3 -OH) 8 (COO) 12 ] SBU applied to gas storage and separation. , Yaghi et al systematically investigated gas and vapor adsorption of rod-shaped LOFs. , We recently also reported a family of rod LOFs for light hydrocarbon separation. , Compared to the discrete and rod-shaped SBUs mentioned above, a three-dimensional (3D) infinite SBU might display the greater potential to preserve the framework integrity during activation as a result of its higher connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…To widen their application scope, it is highly desirable to fabricate robust LOFs with permanent porosity after excluding the guest molecules. To this end, effective methods have been developed, including utilization of discrete highly connected multinuclear clusters and infinite rod-shaped chains as inorganic SBUs. For example, by employing 2-fluorobenzoic acid as a fluorinated modulator, the Eddaoudi group fabricated a series of LOFs on the basis of a 12-connected [Ln 6 (μ 3 -OH) 8 (COO) 12 ] SBU applied to gas storage and separation. , Yaghi et al systematically investigated gas and vapor adsorption of rod-shaped LOFs. , We recently also reported a family of rod LOFs for light hydrocarbon separation. , Compared to the discrete and rod-shaped SBUs mentioned above, a three-dimensional (3D) infinite SBU might display the greater potential to preserve the framework integrity during activation as a result of its higher connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nonthermal-driven separation based on the pressure-swing adsorption of porous materials, taking on low-energy investment, high efficiency, a greener productive procedure, and other various preponderances, has become a promising alternative expected to replace the traditional separation technologies . Although lots of versatile types of porous solid adsorptive materials, such as zeolites, alumina, and carbon-based materials, have been developed for the adsorption and separation of light hydrocarbons, they still are incapable of satisfying the separation requirements of industrial demand because of their puny separation selectivity, poor adsorption capacity, and difficult regeneration. , Metal–organic frameworks (MOFs), as one kind of the most sought-after porous materials in recent decades, have been extensively investigated in the territories of gas storage and/or separation and benefit from their excellent surface areas, high pore volumes, structural diversity, tailorable pore sizes, and tunable functionalities. Up to now, a certain number of MOFs as attractive adsorbents have been confirmed that can be used to effectively separate C 2 H 2 /C 2 H 4 mixtures, and research on them is still in the ascendant. By virtue of a scrupulous survey of reported MOF materials with excellent C 2 H 4 purification performances from C 2 H 2 /C 2 H 4 mixtures, we can concisely summarize a number of appealing features that they possess. (1) Pore sizes can be carefully controlled to fit the dynamic diameter of the target molecule, so as to repel or reduce the adsorption of an improper molecule, and the anticipative molecular sieving effect can be achieved effectively .…”
Section: Introductionmentioning
confidence: 99%
“…The use of fluorinated modulators, such as 2-fba or 2,6-dfba (Figure ), has been widely and successfully implemented in the area of RE MOFs, always with reports of μ 3 -OH-bridged clusters in their structures (Table S1). …”
mentioning
confidence: 99%
“…If the presence of fluorine is indeed confirmed in these RE MOFs, some of the observed properties could be attributed to the fluoro-bridged RE clusters (Table S1). , For example, in a recent report, a terbium hexacluster containing μ 3 -F bridges was compared to the μ 3 -OH-bridged analogue . The fluorinated compound had higher photoluminescence, a property reported in some of these MOFs.…”
mentioning
confidence: 99%